Sexual exploitation of children using cyberspace (Academic Journal of Internal Affairs, 2020)
Well-known crimes have been transformed with the spread of the Internet, and the new forms of crimes challenged the society, especially the justice. This study presents cybercrime-related crimes and behaviours that are not punishable under the Hungarian criminal law, but these still violate basic social norms. Finally, the reader can have a look into a process – through an empirical research – that endangers the minors’ intellectual, moral, and emotional development without physical contact.
Keywords: cyberspace; cybercrime; pornography; children